2021
DOI: 10.21608/ejchem.2019.15430.1962
|View full text |Cite
|
Sign up to set email alerts
|

Purity, Morphological, and Electrical Characterization of Silicon Dioxide from Cogon Grass (Imperata cylindrica) Using Different Ashing Temperatures

Abstract: Cogon grass (Imperata cylindrica) was a detrimental plant and often found in the tropics which contains silicon dioxide. The objective of this study was to extract silicon dioxide from cogon grass and to study the purity, crystal structural, and electrical properties of silicon dioxide from cogon grass. The silica of cogon grass was extracted by washing dry cogon grass using 3% HCl before the burning process, and the ashing temperatures were 500°C, 600°C, and 700°C with a temperature increasing rate of 1°C/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The invasiveness and persistence are related to the biological features, such as extensive rhizome system, adaptability to poor soils and fire, drought tolerance, easy seed dispersal by wind, and high plasticity (MacDonald 2004). In Indonesia, cogongrass populations cover areas of approximately 8.5 million ha (Irzaman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The invasiveness and persistence are related to the biological features, such as extensive rhizome system, adaptability to poor soils and fire, drought tolerance, easy seed dispersal by wind, and high plasticity (MacDonald 2004). In Indonesia, cogongrass populations cover areas of approximately 8.5 million ha (Irzaman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Silica also can be produced from plants such as silica from rice husks and cogon grass [4]- [5] In nature, SiO2 occurs in three forms: quartz, tridymite, and cristobalite, of which the transition temperatures (°C) and specific gravities are given in Table 1. SiO2 melts at 1710°C and forms a transparent cooling glass.…”
Section: Introductionmentioning
confidence: 99%
“…The most regular and commercial use of silica is the primary material for the glass industry and raw material for making solar cells (Burkowicz et al, 2020;Husain et al, 2018). Several studies have shown that natural-based silicas such as silica from bamboo leaf (Aminullah et al, 2018;Irzaman et al, 2018), baggase (Adli et al, 2018), cogon grass (Irzaman et al, 2021), and rice husk (Irzaman et al, 2020;Rohaeti et al, 2010) have been successfully purified and synthesized into silica nanoparticles. Nano-silica is used in science and industrial applications such as catalysts, pigments, pharmaceuticals, drugs, cosmetics, and food (Nabeshi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%